2008
DOI: 10.1007/s10653-008-9193-6
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical transfer and dynamics of iodine in a soil–plant system

Abstract: Radioactive iodide (125I) is used as a tracer to investigate the fate and transport of iodine in soil under various leaching conditions as well as the dynamic transfer in a soil-plant (Chinese cabbage) system. Results show that both soils (the paddy soil and the sandy soil) exhibit strong retention capability, with the paddy soil being slightly stronger. Most iodine is retained by soils, especially in the top 10 cm, and the highest concentration occurs at the top most section of the soil columns. Leaching with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…A couple of recent publications investigated the movements of iodine in the soil, and the percentages of iodine lost from the soil after an enrichment experiment, by means of a radioactive isotope (Weng et al , 2009). The authors concluded that the percentages of iodine lost from the soil by leaching and volatilization were a small fraction of the iodine persisting in the soil, respectively, from 4.5 to 6% and from 4.2 to 4.7% in a sandy soil (Weng et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A couple of recent publications investigated the movements of iodine in the soil, and the percentages of iodine lost from the soil after an enrichment experiment, by means of a radioactive isotope (Weng et al , 2009). The authors concluded that the percentages of iodine lost from the soil by leaching and volatilization were a small fraction of the iodine persisting in the soil, respectively, from 4.5 to 6% and from 4.2 to 4.7% in a sandy soil (Weng et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A couple of recent publications investigated the movements of iodine in the soil, and the percentages of iodine lost from the soil after an enrichment experiment, by means of a radioactive isotope (Weng et al , 2009). The authors concluded that the percentages of iodine lost from the soil by leaching and volatilization were a small fraction of the iodine persisting in the soil, respectively, from 4.5 to 6% and from 4.2 to 4.7% in a sandy soil (Weng et al 2009). Nevertheless, the residual iodine in the soil, particularly fixed in organic forms, as well as the iodine eluviated into surface and groundwater, and the volatilized fractions, could be considered positively to raise the general iodine level in the food chain in the iodine-deficient areas to control IDD ).…”
Section: Discussionmentioning
confidence: 99%
“…Engineered agricultural crops with tailored concentrations of phytonutrients are now regarded as a promising strategy for disease prevention (Johns and Eyzaguirre 2007). Biofortification of carrots or tomatoes is an example of this enrichment protocol with iodine, performed through the addition of compounds containing this element such as KI and KIO 3 Broadley 2005, 2009;Weng et al 2009) to the soil. Iodine, whose deficiency affects 30 percent of the world population, is added universally to table salt; however, total losses before consumption are significant.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we have cultivated iodine-containing vegetables directly by adding algal organic iodized fertilizer into soil and thus realized iodine biofortification of edible vegetable. Using microscopy [18] and localization techniques, we have identified and analyzed the distribution of intracellular iodine which revealed the absorption mechanism of iodine by edible vegetable. The findings show that iodine biofortification is a promising approach for eliminating IDD.…”
mentioning
confidence: 99%